2013
DOI: 10.1111/apm.12210
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal biofilm formation as affected by type acidulant

Abstract: Staphylococcal growth and biofilm formation in culture medium where pH was lowered with weak organic (acetic and lactic) or strong inorganic (hydrochloric) acids were studied. The effects were evaluated by biomass measurements, cell-surface hydrophobicity, scanning electron microscopy (SEM), and confocal laser scanning microscopy (CLSM). The results demonstrated that the inhibition was related to type of acidulant and pH value. At pH 5.0, the antibacterial effect was more pronounced in the presence of acetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…There is some recently published evidence in the literature supporting this hypothesis. [28][29][30] Schwan et al showed that urine is slightly less acidic in the bladder than in the kidneys and the osmolality in the bladder is lower than the osmolality in the kidneys. 28 They suggested that lower acidity (higher pH) and lower osmolality increases type 1 pilus expression in uropathogenic E. coli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some recently published evidence in the literature supporting this hypothesis. [28][29][30] Schwan et al showed that urine is slightly less acidic in the bladder than in the kidneys and the osmolality in the bladder is lower than the osmolality in the kidneys. 28 They suggested that lower acidity (higher pH) and lower osmolality increases type 1 pilus expression in uropathogenic E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that, acidic environment could have important implications for preventing bacterial colonization and control biofilm formation. 30 Based on this evidence, one may assume that there may be a casual relation or facilitative effect between acidity of biological media and tendency to bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…Graphene oxide effect on biofilm formation. The effect of GO on bacterial and C. albicans biofilm formation ability was tested on flat-bottomed polystyrene microtiter plates for (i) biofilm biomass evaluation by the safranin staining method (38) and (ii) the CFU count for the quantification of cultivable cells (37).…”
Section: Methodsmentioning
confidence: 99%
“…The effect of different concentrations of each compound (ranging from MIC to 1/16MIC) on bacterial and C. albicans biofilm-forming ability was tested on polystyrene flat-bottomed microtiter plates, as previously reported (Nostro et al 2014) with some modifications. Briefly, bacterial cultures were grown overnight in TSB, diluted in TSB plus 0.5% (v/v) glucose to 0•5 McFarland and 100 μl was dispensed into each well of 96-well polystyrene flat-bottomed microtiter plates in the presence of 100 μl subinhibitory concentrations (subMIC) of each compound (diluted in TSB plus 0.5% glucose) or 100 μl TSB plus 0.5% glucose (control).…”
Section: Effect On Microbial Biofilm Formationmentioning
confidence: 99%